2020
DOI: 10.20896/saci.v8i2.1059
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Performance of Healthcare Workers During COVID-19 in Pakistan

Abstract: Healthcare workers are one of the most affected communities at the global level during the pandemic of COVID-19, and Pakistan is no exception. Pakistan allocates merely less than 1% of its GDP for the healthcare sector, that is why, in most of the cases, healthcare workers are bound to serve without adopting standard safety measures while dealing with patients. The need for proper Personal Protection Equipment (PPE) has been felt more than ever during the occurrence of COVID-19 due to its quick transferability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
3
2
1
Order By: Relevance
“…Facility-based services were substantially affected during the lockdown, mainly due to suspension of services in areas with positive COVID-19 cases by the state government ( 23 ). In contrast with findings from other studies suggesting lack of training limited health workers’ ability to perform duties during COVID-19 ( 13 , 24 ), most FLWs in our study received training and had good knowledge of COVID-19. Receipt of PPE and incentives were inadequate, however, which hindered effective service provision, which is consistent with findings from other studies in India ( 25 ) and Pakistan ( 13 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Facility-based services were substantially affected during the lockdown, mainly due to suspension of services in areas with positive COVID-19 cases by the state government ( 23 ). In contrast with findings from other studies suggesting lack of training limited health workers’ ability to perform duties during COVID-19 ( 13 , 24 ), most FLWs in our study received training and had good knowledge of COVID-19. Receipt of PPE and incentives were inadequate, however, which hindered effective service provision, which is consistent with findings from other studies in India ( 25 ) and Pakistan ( 13 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with findings from other studies suggesting lack of training limited health workers’ ability to perform duties during COVID-19 ( 13 , 24 ), most FLWs in our study received training and had good knowledge of COVID-19. Receipt of PPE and incentives were inadequate, however, which hindered effective service provision, which is consistent with findings from other studies in India ( 25 ) and Pakistan ( 13 ). Other factors contributing to service reduction included shortages of manpower and supply, increased workload among FLWs, lack of transport, and poor cooperation from beneficiaries.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Lee et al showed that zoom app is becoming increasingly popular amongst nursing students who are learning practical courses [29]. Malso showed that zoom app as the one of the best one for educating especially for nurses students [30]. Correia et al showed Microsoft Teams as the best app for videoconferencing for nursing students [31].…”
Section: Discussionmentioning
confidence: 99%
“…Jika petugas kesehatan diberi sumber daya dan pelatihan yang dibutuhkan, mereka akan melakukan tugasnya dengan cara yang lebih baik. Kurangnya APD, beban pekerjaan yang berlebihan dan kekhawatiran anggota keluarga tertular virus COVID-19 dapat berdampak buruk pada kinerja mereka (Jafar & Shoukat, 2020).…”
Section: Kinerja Tenaga Perawat Selama Pandemi Covid-19unclassified